Judicial Preview (Upaya Menjamin Hak-Hak Konstitusional Warga Negara) - geney srikusuma dewi (Jurnal Yustitia, 2019)
The high intensity of filing cases for judicial review to the Constitutional Court (MK) shows that the legislation product in Indonesia is still far from good. This indicates that the legislators are not able to implement the conception of the formation of good legislation and are not able to accommodate the interests of the people. In this context, this paper offers an idea to examine the constitutionality of a bill (RUU) in the Constitutional Court before it is ratified as a Law. This test is often referred to as Judicial Preview as a form of constitutionality checklist mechanism for the substance of a draft law before it is passed. This research uses the Normative method with a legislative and comparative approach. The results of this study indicate the relevance and opportunity of the Constitutional Court in providing verification of constitutionality values ​​to the bill before it is passed.